Cost Efficiency Analysis Of 36 Chinese Commercial Banks During 2013-2018 - ZHANG, LIN (2019)
This dissertation adopts the SFA method to analyze the cost efficiency of 36 commercial banks in China from 2013 to 2018. At first, this paper takes the change of cost efficiency level as the main research direction and then discusses the cost efficiency score gap under different capital structures. A total of three results have been found. First, the cost efficiency level of China's overall commercial banks has continued to decline over six years. Second, the cost efficiency scores of joint-stock banks (JSCBs) are the highest among the four different types of banks. Finally, foreign banks (FCBs) ranked lowest in average cost efficiency.